Does low-protein diet improve broiler performance under heat stress conditions? - Furlan, Renato Luis [UNESP] (2004)
Nutrition for broilers under high temperatures is extremely important for brazilian broiler chicken industry because the amounts of consumed nutrients and environmental temperature have great effects on bird performance and carcass quality. Among diet nutrients, protein has the highest heat increment; thus, during many years, diets with low protein level were recommended in order to reduce heat production in broiler chickens under heat stress. However, reports have shown that low-protein diets have negative effects on broiler performance when environmental temperature is high, because during heat stress, low food intake associated to a low diet protein induce amino acid deficiencies. Other studies have shown that broilers fed low-protein diets increase their energy requirement for maintenance with higher heat production. Thus, with the growth of broiler industry in tropical areas more challenges need to be faced by the farmers. So, both the ambient and nutritional conditions ought to be well managed to avoid negative effects on poultry production once they can affect the metabolism (body heat production under low temperature and body heat dissipation under high temperature) with consequence on poultry performance (meat and eggs).